The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s40195-017-0691-3
|View full text |Cite
|
Sign up to set email alerts
|

Grain Refinement During Directionally Solidifying GCr18Mo Steel at Low Pulling Speeds Under an Axial Static Magnetic Field

Abstract: The present work investigates how axial static magnetic field affects the solidification structure and the solute distribution in directionally solidified GCr18Mo steel. Experimental results show that grain refinement and the columnar to equiaxed transition is enhanced with the increases in the magnetic field intensity (B) and temperature gradient (G) and the decrease in the growth speed. This phenomenon is simultaneously accompanied by more uniformly distributed alloying elements. The corresponding numerical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The PMF may increase the nucleation rate and increase the probability of nucleus survival. It is generally believed that the electromagnetic force, electromagnetic vibration, and forced convection are favorable for grain refinement, such as a direct action of the electromagnetic force on the mushy zone is supposed to break the dendrites into small fragments owing to high shear stress [20][21][22]. However, it is not clear which mechanism dominates.…”
Section: Refining Mechanism Of the Pmfmentioning
confidence: 99%
“…The PMF may increase the nucleation rate and increase the probability of nucleus survival. It is generally believed that the electromagnetic force, electromagnetic vibration, and forced convection are favorable for grain refinement, such as a direct action of the electromagnetic force on the mushy zone is supposed to break the dendrites into small fragments owing to high shear stress [20][21][22]. However, it is not clear which mechanism dominates.…”
Section: Refining Mechanism Of the Pmfmentioning
confidence: 99%
“…The effect of ASMF on the CET in GCr18Mo steel during directional solidification at low growth speeds (5-20 μm/s) has also been investigated in our previous work. 22) The results have shown that the applied ASMF has enhanced the CET of GCr18Mo steel. However, the mechanism for the CET with ASMF is roughly described from a macro perspective.…”
Section: Introductionmentioning
confidence: 86%
“…More details regarding the experiment conditions are described in the work. 22) The morphology of the solidification microstructures was observed by optical microscopy (DM 6000M, Leica, Germany). The samples were cut-across the longitudinal section, polished, and etched in saturated solution of picric acid at 80°C.…”
Section: Methodsmentioning
confidence: 99%
“…However, under the action of the low-frequency alternating magnetic field, the dendritic structure in the alloy was broken to shorten the length of the primary dendrite, which reduced the distance and difficulty of the residual liquid phase to feed. Studies [40,41] have shown that an equiaxed structure is more conducive to the flow of low melting phases between the crystals to eliminate segregation. When the microstructure of the structure tended to be equiaxed, the eutectic phase exhibited a uniform network distribution.…”
Section: Microscopic Analysismentioning
confidence: 99%